FAKTOR YANG BERHUBUNGAN DENGAN PENGETAHUAN IBU HAMIL PRIMIGRAVIDA DALAM PENGENALAN TANDA BAHAYA KEHAMILAN - Andi Kasrida Dahlan; Andi St. Umrah (Lembaga Penerbit dan Publikasi Ilmiah (LPPI) Universitas Muhammadiyah Palopo, 2017)
Leadership This study aims to determine the factors associated with maternal knowledge primigravid in recognition of pregnancy danger signs in Palopo City Health Center Mungkajang 2016.Design research is a quantitative research with cross sectional. The population is all pregnant women primigravida at health centers Mungkajang Palopo City in 2015. The sample this study were primigravida in health centers Mungkajang Palopo 2015 the number of 35 people with a total sampling sampling techniques. Data retrieval via primary (questionnaires) and secondary. The data is processed using the Statistics Programme For Social Science (SPSS) version 19.0 and analyzed by univariate and bivariate with Chi-square test (X2) and are presented in tabular form distribution and analysis.Bivariate analysis results showed that there was correlation between age, education, and exposure information with knowledge of pregnant women in the introduction primigravid danger signs of pregnancy (P value 0.000 <value α: 0:05), conclusion of this research is that there is correlation between age, education and exposure information to knowledge primigravida pregnant women in recognition of pregnancy danger signs in Health Center Mungkajang Palopo City in 2015, so for health workers, especially midwives further improve and maximize class program of pregnant women each month so that pregnant women can share important information that should be known and understood by pregnant women as danger signs of pregnancy Keywords: Knowledge of, Age, Education, and Information Exposure